The Student’s Physical Behavior Surveyed at a University in Hanoi - Dung, Ha Kim; Hung, Le Ngoc (VNU Journal of Science: Education Research; Vol 40 No 3DO - 10.25073/2588-1159/vnuer.5161, 2024)
According to the approach of systems theory and behaviorism, this paper considers physical behavior as a kind of characteristic behavior of learners in physical education, namely students' physical behavior in physical education and physical exercise in students' daily life. This article uses a literature review method and a survey method at a university in Hanoi to analyze the current situation, influencing factors and consequences of physical behavior conceptualized into the concept of "physical exercise". The article also aims to identify possible problems and suggest solutions to innovate physical education for the physical behavior transformation into the students’ physical habits-for-health to meet the requirements of the physical education quality improvement under the market economy conditions and world integration.